2013
DOI: 10.1002/jgrd.50353
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of satellite and reanalysis products of downward surface solar radiation over East Asia: Spatial and seasonal variations

Abstract: [1] Surface solar radiation plays a crucial role in surface energy and water budgets, and it is also an important forcing for land hydrological models. In this study, the downward surface solar radiation (DSSR) from two satellite products, the Fengyun-2C satellite for daily and monthly data, respectively) and the strongest correlations with OBS (r = 0.90 and 0.93 for daily and monthly data, respectively) among the four products. The DSSR from the reanalyses has much larger RMSEs and generally lower correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 45 publications
(74 reference statements)
6
50
1
Order By: Relevance
“…Figure 8 Lu et al (2011) with 20.4 % daily RMSE and 11.4 % monthly RMSE. Moreover, the daily mean RMSE of our study is obviously lower than that of Jia et al (2013), who estimate SSR with FY-2C and find a daily mean RMSE over China of about 49.3 W m −2 (or 27.5 %). These results suggest that our SSR estimation with MTSAT data works well for various climate regions, land cover types, and elevations.…”
Section: Validation Of Hourly Ssr In the Haihe River Basincontrasting
confidence: 73%
“…Figure 8 Lu et al (2011) with 20.4 % daily RMSE and 11.4 % monthly RMSE. Moreover, the daily mean RMSE of our study is obviously lower than that of Jia et al (2013), who estimate SSR with FY-2C and find a daily mean RMSE over China of about 49.3 W m −2 (or 27.5 %). These results suggest that our SSR estimation with MTSAT data works well for various climate regions, land cover types, and elevations.…”
Section: Validation Of Hourly Ssr In the Haihe River Basincontrasting
confidence: 73%
“…Previous studies have shown that R s from reanalysis data produces significantly less accuracy than satellite-based models [10,[19][20][21]. However, few studies have been focused on the comparison of operational NWP models with satellite-derived data [13,15,[23][24][25][26].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Additionally, NWP models perform a comprehensive simulation of the whole atmospheric system, including ancillary variables such as wind, temperature or relative humidity [18]. However, previous studies have shown that the accuracy achieved using NWP models when computing the surface solar radiation is still significantly less than that obtained using satellite-based models [10,[19][20][21]. In these studies, reanalysis data has usually been used to be contrasted with satellite data, due to the fact that in reanalysis one NWP model with fixed parameters is employed for the entire time series, which improves the temporal consistency of retrieved climate variables [10].…”
Section: Introductionmentioning
confidence: 99%
“…Boilley and Wald [35] conclude that overestimations of R s by MERRA are probably due to the underestimation of cloudy conditions. Jia et al [37] find that R s from the National Centers for Environmental Prediction and National Center for Atmospheric Research Reanalysis (NCEP1) has a poor correlation with field observations, showing a root mean square error of 56.5 W·m −2 over East Asia.…”
Section: Introductionmentioning
confidence: 99%